Readings on Sejahtera MKitchen Entrepreneurship - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Ahmad H.Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohd Ali, Noor Azian; Abdul Aziz, Normaziah; Mohamadali, Noor Azizah; Mahri, Nurhafizah; et al. (mKitchen KICT IIUM, 2022)
This book provides a critical reading on mKitchen entrepreneurship concepts, principles, and practices through five chapters. Chapter 1 deliberates ta‘awun (cooperative behaviour) at IIUM Mkitchen Entrepreneurship project at IIUM and with Masjid Al-Syakirin Gombak (MASG). The outcome is to empower asnaf to optimize the use of masjid as a platform to provide free food, to up skills in foodpreneurship, to create new employment opportunities, to give empowerment, and to nurture entrepreneurship (3Es) for poor and needy people in the surrounding area of it. Chapter 2 deliberates on Sejahtera Business Model on Asnaf foodpreneurship. The model is based on employment, empowerment, and entrepreneurship (3Es). The Sejahtera Business Model is imbued with Tawhidic paradigm, Maqasid al-Shari'ah, and sustainability. The Sejahtera Business Model allows for new employment creation for asnaf and needy people who need employment. Chapter 3 explains the budiman attributes to reinforce sejahtera asnaf entrepreneurship with 3E and Sejahtera Framework. Budiman comprised of adab (virtue), budi (kindness) and sejahtera (peace). Budiman and budiwati have the capacity of bijak berbudi (wisdom in kindness), berani (brave) and bijaksana (full with wisdom). Chapter 4 deliberates on mutual cooperation development. The first phase of mutual cooperation (ta‘awun) among team members is the usrah process which includes ta‘aruf (get to know), tafahum (get to understand), takaful (get to protect) and tanashur (get to love and care) orientation. Chapter 5 explains mKitchen IIUM students' journey in mKitchen by integrating food entrepreneurship with Budi Sejahtera. The students started the journey with in-class training on entrepreneurship, business plan development, digital marketing, and cash management. Then, the students had a cooking demonstration on Turkish delights. One month has been allocated for both process and content phases of training. Then, the students had the pre-internship demonstration at Wadi Budi before a month-long of internship during Ramadan 1443. JEL Classification: M13 and M15